Building a lewis acidic phosphorus - Tay, Madelyn Qin Yi (2016)
This work involves the synthesis and characterization of phosphenium cations whose stability reflects the σ- and π- donating properties of carbone ligands. A coordinatively unsaturated P(III)-containing dication, [iPr2NPC(PPh3)2]2+, has been synthesized and fully characterized by single crystal X-ray diffraction and theoretical calculations. Its reactivity towards DMAP, PMe3, H2O, MeOH, and CoCp2 is presented; no reactions were observed with 2-butyne, dimethylbutadiene and anisole. Two other putative Ph- and Cl-substituted dications [XPC(PPh3)2]2+ were targeted. These could not be observed directly, but evidence for their formation has been obtained through trapping with alkynes and 1,3-dienes to form dicationic species containing phosphirene and phospholene rings, respectively. Reduction of [Me2C2PClC(PPh3)2]2+ with elemental magnesium resulted in the formation of [Me2C2PC(PPh3)2]+, while the dehydrohalogenation of [Me2C4H4PClC(PPh3)2]2+ by 2-methylpyridine resulted in the formation of a phosphole. Preliminary studies on the hydrolysis of the Cl-substituted phosphirenium salt, [Me2C2PClC(PPh3)2]2+ shows a possible formation of a stable phosphirene oxide.